Biological Screening of Zizyphus rugosa and Zizyphus oenoplia extractives (Dhaka University Journal of Pharmaceutical Sciences, 2007)
Different extracts of the leaves and barks of Zizyphus rugosa and Zizyphus oenoplia were studied for their antibacterial, antifungal, and b-glucuronidase inhibitory activities. The methanol extract of Z. rugosa bark showed significant antibacterial activity against Streptococcus pyogens, Staphylococcus aureus and Pseudomonas aerogenes whereas the methanol extract of leaves demonstrated moderate activity against Salmonella typhi. The chloroform and methanol extracts of Z. oenoplia showed good activity against a few bacteria strains. The chloroform extracts of the barks and leaves of Z. rugosaalso showed antifungal activity. The methanol and ethyl acetate extracts of the bark of Z. rugosa revealed significant b-glucuronidase inhibitory activity. Lupeol, betuline, betulinaldehyde and betulinic acid, isolated from Z. rugosa, also showed good activity against a few bacteria.Key words: Zizyphus rugosa, Zizyphus oenoplia, Antibacterial, Antifungal, b-glucuronidase inhibitionDhaka Univ. J. Pharm. Sci. Vol.4(2) 2005The full text is of this article is available at the Dhaka Univ. J. Pharm. Sci. website